Pinpoint pick-up and bubble-free assembly of 2D materials using PDMS/PMMA polymers with lens shapes. (24th April 2019) - Toyoda, Satoshi; Uwanno, Teerayut; Taniguchi, Takashi; Watanabe, Kenji; Nagashio, Kosuke
Abstract: The key to achieving high-quality van der Waals heterostructure devices made by stacking 2D layered materials lies in having a clean interface without interfacial bubbles and wrinkles. In this study, the pinpoint pick-up and transfer system of 2D crystals is constructed using polymers with lens shapes. We report the bubble-free and clean interface assembly of 2D crystals in which unidirectional sweep of the transfer interface precisely controlled with the help of the inclined substrate pushes the bubbles away from the interface.